Analysis of Factors Affecting the Income of Corn Farmers in Kopang District, Central Lombok Regency - Lalu Saparwadi; Muh. Ansyar; Sari Novida (Fin Sinergy: Jurnal Manajemen Keuangan, 2023)
This research aims toanalyze the factors that influence the income of corn farmers in Kopang District, Central Lombok Regency. The dependent variable in this research is the income received by farmers in one farming cycle. Meanwhile, age, education, land area and farming experience are independent variables. Of the 11 villages in Kopang District, 3 villages were selected with the highest number of farmers cultivating corn in Kopang District, namely Wajageseng Village, Bebuak Village, and Kopang Rembiga Village.The number of respondents was determined by Quota Sampling at 30 peopleAndThe determination of respondents in the three (3) villages was determined using Proportional Random Sampling. Based on the results of variance analysis (ANOVA) with the SPSS program, the following regression model was obtainedY = -1,107+24,483X1-13,676X2+7,819X3-7,407X4 where: a = constant, b1 = regression coefficient X1, b2 = regression coefficient X2, b3 = regression coefficient X3 and b4 = regression coefficient X4. X1= Age, X2= Education X3= Land Area and X4= Farming Experience.Results of variance analysis (F test)with the SPSS program at a confidence level of 95%,shows that the four variables are independent: age, education, land area, and farming experience(X1, Meanwhile, the partial test (t test) shows that there is one independent variable that partially has a significant effect on the income of corn farmers in Kopang District, Central Lombok Regency, namely the land area variable (X3).